Forensic aspects of hypoglycaemia - Marks, Vincent (Boca Raton : CRC Press, 2018)
The Forensic Aspects of Hypoglycaemia succinctly covers the medicolegal considerations of hypoglycaemia in a variety of scenarios including driving fatalities, petty crime, homicide and suicide. Covering the definitions and diagnosis of hypoglycaemia to its bearing on criminal behavior, this book draws on the author's extensive experience and contains a wealth of information for physicians and lawyers, including cases from the author's past and notable cases in the public domain.
The control of blood glucose in health and disease : hypoglycaemia -- Petty crime -- Violence and aggression -- Accident and negligence -- Spontaneous (or non-iatrogenic) hypoglycaemia -- Driving offences -- Hypoglycaemia from drugs -- Forensic investigation of hypoglycaemia -- Factitious hypoglycaemia and suicide -- Murder -- Munchausen by proxy : infanticide and murder of children -- Murder and attempted murder by carers with insulin -- Confessions -- Frequently asked questions -- Expert witness.
OCLC-licensed vendor bibliographic record.
Keywords: Hypoglycemia; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; LAW / Forensic Science; MEDICAL / Endocrinology & Metabolism